2020
DOI: 10.1038/s41598-020-72535-0
|View full text |Cite
|
Sign up to set email alerts
|

Intensity harmonization techniques influence radiomics features and radiomics-based predictions in sarcoma patients

Abstract: Intensity harmonization techniques (IHT) are mandatory to homogenize multicentric MRIs before any quantitative analysis because signal intensities (SI) do not have standardized units. Radiomics combine quantification of tumors’ radiological phenotype with machine-learning to improve predictive models, such as metastastic-relapse-free survival (MFS) for sarcoma patients. We post-processed the initial T2-weighted-imaging of 70 sarcoma patients by using 5 IHTs and extracting 45 radiomics features (RFs), namely: c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…The intraclass correlation coefficient (ICC) was the statistical method used in most of the papers reporting a reproducibility analysis [ 13 , 15 18 , 20 , 22 25 , 27 29 , 31 ]. ICC threshold ranged between 0.6 [ 13 ] and 0.9 [ 22 ] for reproducible features.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intraclass correlation coefficient (ICC) was the statistical method used in most of the papers reporting a reproducibility analysis [ 13 , 15 18 , 20 , 22 25 , 27 29 , 31 ]. ICC threshold ranged between 0.6 [ 13 ] and 0.9 [ 22 ] for reproducible features.…”
Section: Resultsmentioning
confidence: 99%
“…In 16 (33%) investigations [13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], the reproducibility of radiomic features was assessed on the basis of repeated segmentations performed by different readers and/or the same reader at different time points. Two (4%) studies presented an analysis to assess the reproducibility based on different acquisition [30] or post-processing [31] techniques. Of note, segmentations were validated by a second experienced reader in 15 studies [12,[32][33][34][35][36][37][38][39][40][41][42][43][44][45] without, however, addressing the issue of radiomic feature reproducibility.…”
Section: Reproducibility Strategiesmentioning
confidence: 99%
“…However, the subsequent downstream effects of standardization may be substantial when human eyes no longer become the driving force of analysis. For instance, Crombé et al demonstrated marked differences in radiomic outcome prediction performance using different intensity standardization methods 42 . We have performed a preliminary radiomic feature analysis comparing intensity standardization methods in Supplementary Data S6 which generally follows the trends highlighted in our study, but further work is needed to determine effects on HNC-specific outcome prediction tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the robust features often resulted to have low diagnostic performance [ 16 ]. In addition, applying a post-reconstruction batch harmonization has been also proposed to reduce the variability among centers by using global scaling, in which signal intensities are harmonized by eliminating the mean and the unit variance is downsized; z-standardization, where each feature is normalized considering the mean and standard deviation by providing some comparable results; and histogram-matching, by transforming intensity histogram in order to combine them and find the reference histogram [ 17 ]. However, each method has different advantages and drawbacks, and they should be weighted in different clinical scenarios.…”
Section: Technical Principlesmentioning
confidence: 99%